2021
DOI: 10.3389/fcimb.2021.700191
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Coxsackievirus A6 Strains Isolated From Children With Hand, Foot, and Mouth Disease

Abstract: Coxsackievirus A6 (CVA6) is a key pathogen causing hand, foot and mouth disease (HFMD). However, there are currently no specific antiviral drugs or vaccines for treating infections caused by CVA6. In this study, human rhabdomyosarcoma (RD), African green monkey kidney (Vero), and human embryonic lung diploid fibroblast (KMB17) cells were used to isolate CVA6 from 327 anal swab and fecal samples obtained during HFMD monitoring between 2009 and 2017. The VP1 genes of the isolates were sequenced and genotyped, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Similar to the other members of the Picornaviridae family, CV-A6 has a single-stranded, positive-sense RNA genome. It can be segregated into 4 genotypes, designated as A, B, C, and D, and further subdivided into the B1 and B2, C1 and C2, and D1, D2, and D3 subgenotypes (15). In recent years, the D3 and E2 strains have become prevalent in China, France, Spain, Japan, and other countries to varying degrees (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the other members of the Picornaviridae family, CV-A6 has a single-stranded, positive-sense RNA genome. It can be segregated into 4 genotypes, designated as A, B, C, and D, and further subdivided into the B1 and B2, C1 and C2, and D1, D2, and D3 subgenotypes (15). In recent years, the D3 and E2 strains have become prevalent in China, France, Spain, Japan, and other countries to varying degrees (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that CVA6 exhibits a strong muscle tropism, which may be one of the direct causes of paralysis and inability to obtain breast milk in newborn mice, thus accelerating their death. Previous studies confirmed that skeletal muscle was the most important site for CVA6 virus replication [ 20 , 28 , 39 , 47 ]. Other studies have suggested that skeletal muscle is the leading site for the replication of Enterovirus infection, providing the source of virus for CNS infection [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, establishing animal models with typical clinical symptoms is one of the important steps to understanding the pathogenesis of CVA6 infection and the development of vaccines, therapeutic antibodies, and antiviral drugs. Recently, several animal models [ 20 , 27 , 28 , 39 ] have been reported to evaluate vaccines and antiviral drugs and study the pathogenesis. However, those CVA6 animal models differ from our model in several important respects, namely the dose and route of inoculation, the strain of laboratory mice used, and, critically, the virus strain used.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations of HFMD include mild to severe rash, herpangina, pulmonary edema, circulatory disturbances, meningitis, aseptic encephalitis, and even death ( Wang et al, 1999 ; Solomon et al, 2010 ). Since 2012, outbreaks associated with CVA6 have been frequently reported in Europe, Japan and some developed regions of China ( Feng et al, 2015 ; Kanbayashi et al, 2017 ; Kamau et al, 2021 ; Liu et al, 2021 ; Tomba Ngangas et al, 2022 ). From then on, CVA6 has been gradually predominant in most areas of China since 2013 ( He et al, 2021 ; Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2012, outbreaks associated with CVA6 have been frequently reported in Europe, Japan and some developed regions of China ( Feng et al, 2015 ; Kanbayashi et al, 2017 ; Kamau et al, 2021 ; Liu et al, 2021 ; Tomba Ngangas et al, 2022 ). From then on, CVA6 has been gradually predominant in most areas of China since 2013 ( He et al, 2021 ; Liu et al, 2021 ). Our former study found CVA6 increasingly predominated in local HFMD cases, and EV-A71 was no longer detected from HFMD surveillance after 2 years EV-A71 vaccine promotion and implementation ( He et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%